Development of a 100 J, 10 Hz laser for compression experiments at the High Energy Density Instrument at the European XFEL - Mason, Paul (My University, 2018)
This data set contains wavefront (HASO .has file), far-field beam quality (.pgm) and energy stability (excel) data from DiPOLE used in this publication.
Keywords: DPSSL, high energy lasers, Yb:YAG, cryogenic lasers, laser amplifiers